Compound‐specific bromine isotope ratio analysis using gas chromatography/quadrupole mass spectrometry. (5th August 2016) - Zakon, Yevgeni; Halicz, Ludwik; Lev, Ovadia; Gelman, Faina
Abstract : Rationale: Brominated organic compounds (BOCs) are common persistent toxic pollutants. Compound‐specific stable bromine isotope ratio analysis is one of the potential approaches for investigating BOC transformations in the environment. In the present study, we demonstrate that precise bromine isotope analysis of BOCs can be successfully performed by gas chromatography/quadrupole mass spectrometry (GC/qMS) systems that are widely available in analytical laboratories. Methods: Optimization and validation of the GC/qMS method were performed by analysis of bromoform, 3‐bromophenol and 4‐bromotoluene. In addition, comparison of the results obtained by GC/qMS and GC/multi‐collector inductively coupled plasma mass spectrometry (MC‐ICPMS) for 1, 2‐dibromoethane and 3‐bromophenol samples with different bromine isotope composition was carried out to evaluate the analytical performance of the developed method. Results: Precisions in the range 0.2–0.3‰ were attained for sample amounts in the range of tens to thousands pmol. Good correlation between the results obtained by GC/qMS and GC/MC‐ICPMS for laboratory standard materials (1, 2‐dibromoethane and 3‐bromophenol) (regression coefficient R 2 > 0.98) was achieved. Conclusions: The GC/qMS method for bromine isotope analysis shows a good performance and can be applied routinely for studying transformations of BOCs. Due to the observed dependence of the measured isotope ratios on the amount of the analyte and the calculation scheme applied, normalization of the results versus appropriate standards is required for source attribution applications. Copyright © 2016 John Wiley & Sons, Ltd.